2019
DOI: 10.1042/bsr20192590
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between red cell distribution width and prognosis of patients with osteosarcoma

Abstract: We retrospectively collected the clinical data and follow-up information of patients with osteosarcoma who were admitted to Department of Orthopedics, RenMin Hospital of Wuhan University from January 2010 to December 2016 and explore the relationship between red cell distribution width (RDW) and prognosis of patients with osteosarcoma. The present study finally included 271 patients with osteosarcoma with median follow-up time of 24.2 months (3–69 months). According to the RDW median, 135 patients belong to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Likewise, the prognostic role of NLR before treatment has been confirmed in different solid tumours [ 13 ], including STS [ 15 ]. On the other hand, high RDW has also been previously reported as a predictive factor in different tumours [ 21 ], including some types of sarcomas, such as osteosarcomas [ 20 ], but SFT patients were not included in these studies. In our study, other clinicopathological factors retrospectively explored, such as the presence of necrosis, MFI ≤ 8 months, and number of mitoses > 3/10 hpf or tumour size at diagnosis > 85 mm and ECOG > 1, were associated with statistically significant worse PFS or OS, respectively, in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the prognostic role of NLR before treatment has been confirmed in different solid tumours [ 13 ], including STS [ 15 ]. On the other hand, high RDW has also been previously reported as a predictive factor in different tumours [ 21 ], including some types of sarcomas, such as osteosarcomas [ 20 ], but SFT patients were not included in these studies. In our study, other clinicopathological factors retrospectively explored, such as the presence of necrosis, MFI ≤ 8 months, and number of mitoses > 3/10 hpf or tumour size at diagnosis > 85 mm and ECOG > 1, were associated with statistically significant worse PFS or OS, respectively, in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high NLR values have been also associated with adverse survival in many solid tumours [ 12 , 13 , 14 ] and metastasis at diagnosis in STS [ 15 ]. Other peripheral inflammatory indexes, such as high platelet/lymphocyte ratio (PLR), have been associated with worse survival in STS [ 16 ] and other solid tumours [ 17 ] or high red cell distribution width (RDW), which has been associated with worse OS in solid tumours, including osteosarcomas [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of RDW has been reported in not only cardiovascular disease, but also cancer prognosis. High RDW are associated with unfavorable survival in many types of cancers including breast cancer ( 14 ), hematological tumor ( 15 ), gynecological cancer ( 16 , 17 ), and osteosarcoma ( 18 ). Although there is no clear explanation of the relationship between RDW and cancer prognosis, RDW can be a promising biomarker for assessment of the risk of CTRCD and cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Hb can reflect the nutritional status of the body, the immune status of the organism, and decreased Hb has been shown to be associated with poor prognosis in pancreatic neuroendocrine tumors, esophageal cancer, and oral cancer, [7][8][9] and erythrocyte distribution width is a parameter that reflects the heterogeneity of erythrocyte volume, and previous studies have found that it may be a potential predictor of osteosarcoma, CRC, and breast cancer. [10][11][12] The hemoglobin/erythrocyte distribution width ratio (HRR) is a new marker with higher sensitivity and specificity compared to Hb and RDW alone, and better predicts the level of inflammation in patients at an early stage. Recently, a retrospective study confirmed a positive correlation between HRR and prognosis of patients with primary liver cancer.…”
Section: Introductionmentioning
confidence: 99%